2015
DOI: 10.4155/fso.15.72
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Prostate Cancer: Present Challenges and Future Opportunities

Abstract: Prostate cancer (PCa) has variable biological potential with multiple treatment options. A more personalized approach, therefore, is needed to better define men at higher risk of developing PCa, discriminate indolent from aggressive disease and improve risk stratification after treatment by predicting the likelihood of progression. This may improve clinical decision-making regarding management, improve selection for active surveillance protocols and minimize morbidity from treatment. Discovery of new biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 173 publications
0
25
0
Order By: Relevance
“…The common thread observed in these studies is that more than 90% of these investigations are conducted in MEA. As a result, significant strides have been made in the design of serum and urine diagnostic biomarkers, whereby some are currently clinically applicable as mentioned earlier and these were recently reviewed in Sharma et al Some include (a) the noncoding RNA, PCA3 that is believed to be overexpressed in 95% of PCa cases in MEA, presents in high levels in some men but is unaccompanied by malignancy meanwhile additional studies confirmed an association of this biomarker in Chinese men; b) the kallikrein panel (comprises of total PSA, free PSA, intact PSA and human kallikrein‐related peptidase 2 (KLK2)) was reported to improve the predictive accuracy of PCa detection over PSA alone with a reduction in the biopsy rate by 362 for every 1000 men with elevated PSA and these studies were primarily conducted on MEA; (c) TMPRSS2: ERG fusion & β‐microseminoprotein, identification of the fusion gene in urine was reported to enhance PCa detection by more than 90% specificity and 94% predictive value, a research that began by Tomlins and later a GWAS study reported in Germany and across other ethnicities, confirmed the importance of this biomarker among MEA, conversely, other studies did not reveal the ethnicity of the men investigated although given the geographical locale, it is believed they too are primarily of a European ancestry and (d) DNA methylation of genes, for example a) Glutathione ‐S‐Transferase‐Pi (GSTP1) that is involved in DNA detoxification and cell cycle regulation, to the best of our knowledge no GWAS research has been conducted on this epigenetic biomarker but smaller studies conducted in Germany, Korea, Italy and meta‐analysis on MAA in America, the Caribbean and in Africa have confirmed an association of this protein to an elevated risk of PCa; b) the promoter region of adenomatous polyposis coli (APC) that is involved in cell apoptosis, migration and adhesions have been associated with PCa occurrence among Chinese, Italians, Pakistanis and other ethnicities, furthermore, fairly recent meta‐analysis that covered seven studies (1227 patients for North America and Europe) calculated the pooled hazard ratio to be 1.74 that correlates methylated APC to unfavorable impact on biochemical recurrence of PCa confirming the PCa prognostic potential of this biomarker as well, and; c) the putative tumor suppressor Ras‐associated domain family 1 A (RASSF1A) whereby meta‐analysis conducted on 1123 cases primarily in MEA associated the hypermethylation of CpG islands within the promoter region of these genes to PCa . Research has also demonstrated that PCA3, TMPRSS2:ERG fusion and PTEN among others possess PCa prognostic poten...…”
Section: Causes For Prostate Cancer Disparitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The common thread observed in these studies is that more than 90% of these investigations are conducted in MEA. As a result, significant strides have been made in the design of serum and urine diagnostic biomarkers, whereby some are currently clinically applicable as mentioned earlier and these were recently reviewed in Sharma et al Some include (a) the noncoding RNA, PCA3 that is believed to be overexpressed in 95% of PCa cases in MEA, presents in high levels in some men but is unaccompanied by malignancy meanwhile additional studies confirmed an association of this biomarker in Chinese men; b) the kallikrein panel (comprises of total PSA, free PSA, intact PSA and human kallikrein‐related peptidase 2 (KLK2)) was reported to improve the predictive accuracy of PCa detection over PSA alone with a reduction in the biopsy rate by 362 for every 1000 men with elevated PSA and these studies were primarily conducted on MEA; (c) TMPRSS2: ERG fusion & β‐microseminoprotein, identification of the fusion gene in urine was reported to enhance PCa detection by more than 90% specificity and 94% predictive value, a research that began by Tomlins and later a GWAS study reported in Germany and across other ethnicities, confirmed the importance of this biomarker among MEA, conversely, other studies did not reveal the ethnicity of the men investigated although given the geographical locale, it is believed they too are primarily of a European ancestry and (d) DNA methylation of genes, for example a) Glutathione ‐S‐Transferase‐Pi (GSTP1) that is involved in DNA detoxification and cell cycle regulation, to the best of our knowledge no GWAS research has been conducted on this epigenetic biomarker but smaller studies conducted in Germany, Korea, Italy and meta‐analysis on MAA in America, the Caribbean and in Africa have confirmed an association of this protein to an elevated risk of PCa; b) the promoter region of adenomatous polyposis coli (APC) that is involved in cell apoptosis, migration and adhesions have been associated with PCa occurrence among Chinese, Italians, Pakistanis and other ethnicities, furthermore, fairly recent meta‐analysis that covered seven studies (1227 patients for North America and Europe) calculated the pooled hazard ratio to be 1.74 that correlates methylated APC to unfavorable impact on biochemical recurrence of PCa confirming the PCa prognostic potential of this biomarker as well, and; c) the putative tumor suppressor Ras‐associated domain family 1 A (RASSF1A) whereby meta‐analysis conducted on 1123 cases primarily in MEA associated the hypermethylation of CpG islands within the promoter region of these genes to PCa . Research has also demonstrated that PCA3, TMPRSS2:ERG fusion and PTEN among others possess PCa prognostic poten...…”
Section: Causes For Prostate Cancer Disparitiesmentioning
confidence: 99%
“…[75][76][77][78][79][80][81][82][83] The common thread observed in these studies is that more than 90% of these investigations are conducted in MEA. As a result, significant strides have been made in the design of serum and urine diagnostic biomarkers, whereby some are currently clinically applicable as mentioned earlier and these were recently reviewed in Sharma et al 86 Some include (a) the noncoding RNA, PCA3 that is believed to be overexpressed in 95% of PCa cases in MEA, 76,86 presents in high levels in some men but is unaccompanied by malignancy meanwhile additional studies confirmed an association of this biomarker in Chinese men 87,88…”
Section: Molecular Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, molecular alterations detected in urine, serum, peripheral blood and/or tissue samples of PC patients have been found and suggested for use in determining PC diagnosis and prognosis . mRNA expressions of a specific long noncoding RNA, prostate specific antigen 3 ( PCA 3), and serine 2 ( TMPRSS2 ): erythroblastosis virus E26 oncogene homolog ( ERG ) gene ( TMPRSS2 ‐ ERG , T2E ) fusion, a specific molecular alteration of PC, are recommended for analysis in urine, peripheral blood, and/or tissue samples for diagnosis and/or modulating the timing of a repeat biopsy when PC is suspected .…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, molecular alterations detected in urine, serum, peripheral blood and/or tissue samples of PC patients have been found and suggested for use in determining PC diagnosis and prognosis. [18][19][20][21] mRNA expressions of a specific long noncoding RNA, prostate specific antigen 3 (PCA3), and serine 2 (TMPRSS2): erythroblastosis virus E26 oncogene homolog (ERG) gene (TMPRSS2-ERG, T2E) fusion, a specific molecular alteration of PC, are recommended for analysis in urine, peripheral blood, and/or tissue samples for diagnosis and/or modulating the timing of a repeat biopsy when PC is suspected. 18,[22][23][24][25][26] Even though these are the best-known diagnostic molecular markers of PC, different scenarios concerning cut-off values may emerge dependent on the patients' histopathological features including the presence of suspicious lesions such as ASAP or high grade prostatic intraepithelial neoplasia (HGPIN) and clinicopathological characteristics including abnormal DRE and/or elevated PSA levels thought to be pathological.…”
Section: Introductionmentioning
confidence: 99%